Digital and analog hybrid precoding technology combined with V-BLAST in multi-user massive MIMO system - Shuai ZHANG; Jinlong ZHAN; Man WANG; Minjie LI (Dianxin kexue)
In the massive MIMO system, the only full digital baseband precoding（FD-BP）scheme（such as full complexity zero forcing）requires the same number of radio frequency（RF）chains as the number of antenna elements, which leads to extreme high hardware cost, the hybrid precoding can reduce the number of RF chain heavily and approach the performance of the FD-BP, so the hybrid precoding for massive MIMO is necessary and worth studying. The adaptive digital and analog hybrid precoding（AHP）can further reduce the hardware complexity compared with the conventional digital and analog hybrid precoding （conventional hybrid precoding）and which combined with V-BLAST can get the array gain and multiplexing gain simultaneously. Simulation results confirm the proposed scheme can obtain the higher spectral efficiency, the lower hardware complexity and more ideal BER performance.